2010
DOI: 10.1111/j.1469-8137.2009.03137.x
|View full text |Cite
|
Sign up to set email alerts
|

Presence of three mycorrhizal genes in the common ancestor of land plants suggests a key role of mycorrhizas in the colonization of land by plants

Abstract: Summary• The colonization of land by plants fundamentally altered environmental conditions on earth. Plant-mycorrhizal fungus symbiosis likely played a key role in this process by assisting plants to absorb water and nutrients from soil.• Here, in a diverse set of land plants, we investigated the evolutionary histories and functional conservation of three genes required for mycorrhiza formation in legumes and rice (Oryza sativa), DMI1, DMI3 and IPD3.• The genes were isolated from nearly all major plant lineage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
196
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(205 citation statements)
references
References 53 publications
8
196
1
Order By: Relevance
“…Our results support the hypothesis of Wang et al (2010) and Delaux et al (2013) that genes that are important for AM symbiosis were already present in a common ancestor of land plants, and remained conserved in most plants until today. In M. truncatula mutants lacking MtPT4, a phosphate transporter (PHT) located in the periarbuscular membrane and essential for symbiotic Pi transport (Harrison et al 2002), arbuscules are prematurely degenerated and the symbiosis is not maintained (Javot et al 2007).…”
Section: Am-inducible Amts Are Conserved In the Poaceaesupporting
confidence: 88%
“…Our results support the hypothesis of Wang et al (2010) and Delaux et al (2013) that genes that are important for AM symbiosis were already present in a common ancestor of land plants, and remained conserved in most plants until today. In M. truncatula mutants lacking MtPT4, a phosphate transporter (PHT) located in the periarbuscular membrane and essential for symbiotic Pi transport (Harrison et al 2002), arbuscules are prematurely degenerated and the symbiosis is not maintained (Javot et al 2007).…”
Section: Am-inducible Amts Are Conserved In the Poaceaesupporting
confidence: 88%
“…Like the rhizobium-legume symbiosis, Ca2+ oscillations were detected in dmi3 but not in dmi1 and dmi2 Medicago mutants in response to AMFs that support the hierarchical distribution of the SYM pathway with the nuclear kinase DMI3 located downstream as the decoder of the calcium spiking [24 and 30]. On the one hand, it seems evolutionary convenient that the same subset of genes, which are common in plant taxa [ 31] and have been shown to function in mycorrhizal signaling in non-legumes [ 32], could control two diverse biological systems. On the other hand, this common response again raises the problem of specificity: how do legumes distinguish between AMFs and rhizobia and organize the appropriate accommodation of the microbe inside the root tissues?…”
Section: How Are Symbiotic Signals Transduced?mentioning
confidence: 84%
“…While many liverworts (outlined above) and hornworts [30,31] exhibit interactions with mycorrhizal fungi, mosses generally do not form mycorrhizae [32,33]; for a recent and comprehensive overview see [29]. That mosses do not form mycorrhizae is further corroborated by Wang and colleagues [34], who showed that moss arbuscular mycorrhizal symbiosis genes show high sequence divergence as compared to their homologous counterparts in all other land plants. Yet, in light of the recently supported monophyly of the bryophytes [35], the phenomenon that mosses do not form mycorrhizae likely represents a case of secondary loss [29].…”
Section: Fungal Symbioses Exemplify Ancient Plant-microbe Interactionsmentioning
confidence: 93%
“…On balance, symbiosis with arbuscular mycorrhizal fungi appears to be an ancestral feature of all land plants [36]. Indeed, molecular data presented by Wang et al [34] indicate that genes associated with interactions with mycorrhizal fungi were likely present in the last common ancestor of land plants, which was corroborated by Delaux et al [18]. But what about the algal progenitors of land plants?…”
Section: Fungal Symbioses Exemplify Ancient Plant-microbe Interactionsmentioning
confidence: 98%